The International Criminal Court and the End of Impunity in Kenya - Nichols, Lionel (Springer, 2015)
The period immediately following Kenya's 2007 presidential election left a shocking trail of atrocities, with over 1,000 people dead and countless thousands left victimised and displaced. In response, the International Criminal Court began a series of investigations and trials, promising no impunity for even the highest ranking perpetrators. When the country's president and vice-president were implicated in the crimes, the case took on worldwide significance.